Association between fetal myocardial performance index and fetal heart rate monitoring: a prospective observational cohort study. (3rd April 2019) - Gimovsky, Alexis C.; Whitney, Brianne; Wood, Dennis; Weiner, Stuart
Abstract: Objective: To evaluate whether the left myocardial performance index (MPI) changes in association with the fetal heart rate (FHR) tracing during labor. Study design: Women with term, singleton pregnancies, in labor were recruited to this prospective cohort study. Primary outcome: difference in left MPI between Category of fetal heart rate tracings. Secondary outcomes: differences in left MPI by FHR characteristics. Participants underwent ultrasound examination, during which fetal MPI was measured. Results: Twenty-four laboring patients were recruited. There were 13 patients with Category I FHR, 11 patients with Category II FHR, and 0 patients with Category III FHR. Demographics were similar between the groups. MPI was not significantly different between fetuses with Category I or Category II FHR (0.67 versus 0.65, p = .385). MPI was significantly higher in fetuses with accelerations versus those without (0.71 versus 0.59, p = .045). MPI was not significantly different for fetuses with or without decelerations (0.65 versus 0.68, p = .350), between deceleration type (0.50 versus 0.64 versus, 0.75, p = .421), or between variability type (0.56 versus 0.68, p = .113). Conclusions: MPI of fetuses in term, laboring patients did not vary with differing FHR characteristics except for the presence or absence of accelerations.